Deontological Study of the Binding Strength of Precontractual Promises: A Legal and Ethical Approach - Siregar, Mahmul; Siregar, Fitri Yanni Dewi; Rafiqi, Rafiqi; Muniifah, Nur (JURNAL AKTA, 2025)
This study analyzes the binding force of pre-contractual promises from the perspective of deontological law and ethics. In contract law, pre-contractual promises often raise debates about their validity and legal consequences. This study uses a normative legal approach with descriptive qualitative analysis, which focuses on the analysis of legal norms governing pre-contractual promises. From a deontological ethics perspective, the fulfillment of a promise is considered a moral obligation that must be honored regardless of the consequences, based on the principles of honesty and integrity. This study highlights that the combination of deontological law and ethics approaches can provide a stronger normative basis for assessing pre-contractual obligations, increase legal certainty, and strengthen the principle of trust in business relationships and contractual negotiations. Deontological studies of the binding force of pre-contractual promises confirm that promises made before a formal contract have interrelated legal and ethical dimensions. From a legal perspective, although not always legally binding, the principle of promissory estoppel in common law and the principle of good faith in civil law can provide protection for parties who suffer losses due to unfulfilled pre-contractual promises. Meanwhile, from a deontological ethical perspective, the obligation to fulfill promises is based on universal moral principles, such as honesty and good faith, which form the basis of trust in business and legal interactions.